Deformation detection algorithm of shallow and large-span tunnel support structure based on wireless sensor network. Issue 4 (14th October 2020) - Wu, Huawei; Sun, Chuan; Li, Yicheng; Kuang, Yong
In order to improve the safety of tunnel support structure, a deformation detection algorithm based on wireless sensor network is proposed. The wireless sensor network nodes were deployed with the randomly distributed autonomous network grid structure, and the deformation force parameters of the support structures of shallow span and large span tunnels were obtained with the pressure sensor, and the power spectrum characteristic quantities of the sensor parameters were extracted. The time-frequency characteristic decomposition method is used to realise the beamforming processing deformation parameters. The quantitative analysis ability of the improved structure deformation is detected according to the detection of deformation amplitude and the estimation of related parameters. The experimental results show that the detection accuracy of the method is improved from 87% to 100%, and the detection performance is improved, which verifies the effectiveness of the method.